Diffusion Tensor Imaging of Peripheral Nerves - Naraghi, Ali M.; Awdeh, Haitham; Wadhwa, Vibhor; Andreisek, Gustav; Chhabra, Avneesh (Seminars in Musculoskeletal Radiology, 2015)
Diffusion tensor imaging (DTI) is a powerful MR imaging technique that can be used to probe the microstructural environment of highly anisotropic tissues such as peripheral nerves. DTI has been used predominantly in the central nervous system, and its application in the peripheral nervous system does pose some challenges related to imaging artifacts, the small caliber of peripheral nerves, and low water proton density. However advances in MRI hardware and software have made it possible to use the technique in the peripheral nervous system and to obtain functional data relating to the effect of pathologic processes on peripheral nerves. This article reviews the imaging principles behind DTI and examines the literature regarding its application in assessing peripheral nerves.
Keywords: diffusion tensor imaging; MRI; peripheral nerves; MRN